Plant Growth Promoting Actinobacteria, the Most Promising Candidates as Bioinoculants? - Boukhatem, Zineb Faiza; Merabet, Chahinez; Tsaki, Hassini (Frontiers in Agronomy, 2022)
Plant Growth Promoting Bacteria (PGPBs) are a strong ally for sustainable agriculture. They offer an interesting alternative to chemical fertilizers and pesticides. Many microorganisms have been widely documented for their PGPR traits, but actinobacterial microbes which have been increasingly documented only these two past decades for their ability to promote plant growth. Their action on plant health and yield could be either direct, indirect or both. This review will cover articles that have been published on Actinobacteria PGP traits, highlighting the involved mechanisms to reveal their strong potential as microbial fertilizers. Possible strategies to encourage Actinobacteria use as bioinoculants are also discussed.